Ethics: What is the Research Scenario in the Brazilian Symposium SBSC? - Carvalho, Luiz Paulo; Suzano, José Antonio; Oliveira, Jonice; França, Juliana Baptista dos Santos; Santoro, Flávia Maria (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2022: Anais do XVII Simpósio Brasileiro de Sistemas Colaborativos, 2022)
Ethics is a human construction, therefore historical, social and cultural. It is impossible to conceive Collaborative Systems without thinking about ethics, because this is manifested in the practices between us. The largest academic-scientific event dedicated to the field of CS in Brazil is the Brazilian Symposium on Collaborative Systems. Through a Systematic Literature Review, we aim to answer the question: what is the panorama of the explicit occurrence of ethical aspects in the publications of the main track of the SBSC? Considering the importance of ethics associated with free, conscious and intentional human practice in a collective and collaborative scope, how are ethical aspects considered, if any, in the communications of these researches? In this sense, what was initially proposed as an Systematic Literature Review became a stimulus to reflection, why are ethical aspects neglected? More than that, is there any way to improve ethical deliberation or is this neglect a symptom of the current political-scientific state of the event?